Preparation method of composite olivine structure positive electrode material
By using a ternary composite olivine structure coated with iron, cobalt and manganese in the positive electrode material of lithium ion battery, the problems of high production cost, high toxicity and capacity loss of positive electrode materials in the prior art are solved, and the further development is achieved Stable and safe battery performance.
Patent Information
- Application Number
- CN202411446399.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-14
AI Technical Summary
The existing lithium-ion battery positive electrode materials have problems such as high production costs, high toxicity and high capacity loss in the first discharge cycle.
The ternary composite olivine structure positive electrode material coated with iron, cobalt and manganese by stirring, heating, ball milling, spray drying and calcining is prepared, and a modified lithium metal phosphate material structure is formed to build a multi-dimensional conductive network.
It reduces the production cost of electrode materials, reduces toxicity, improves the circulation and safety performance of the material, and solves the problem of high capacity loss in discharge cycles.
Smart Images

Figure CN119430305A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery material preparation, and in particular to a method for preparing a composite olivine structure positive electrode material. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices due to their high energy density, low self-discharge and small memory effect. The early electrode material was LiCoO2, but it had prominent cost, toxicity and safety issues. Later, derivatives with similar structures such as LiNiO2, LiMnO2 and LiMn2O4 appeared. The synthesis of LiNiO2 forms a NiO2 phase, which causes the capacity to drop rapidly. Under high temperature conditions, the exothermic decomposition of LiNiO2 in the charging state leads to safety issues. 3+ Due to the Jahn-Teller distortion, the dissolution of Mn ions in the electrolyte, the formation of two cubic phases and the growth of microstrain, LiMnO2 is thermodynamically unstable and will be rapidly converted into LiMn2O4 during the cycle process, while LiMn2O4 will experience severe capacity decay at high temperatures.
[0003] In the prior art, lithium nickel cobalt manganese oxide Li(NiMnCo)O2 is usually used as a substitute to address the problems of traditional battery materials. Li(NiMnCo)O2 material has the advantages of high capacity and good thermal stability, but it also has inherent disadvantages of relatively high cost, high toxicity and high capacity loss in the first discharge cycle. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for preparing a composite olivine structure positive electrode material to solve the problems of relatively high production cost, high toxicity and high capacity loss in the first discharge cycle existing in the prior art.
[0005] To achieve the above object, the present invention provides a method for preparing a composite olivine structure positive electrode material, comprising the following steps:
[0006] S1: adding ethanol as a solvent to a stirred tank, adding a carbon source to the ethanol solvent during continuous stirring, and stirring evenly to completely dissolve the carbon source in the ethanol solvent to form an ethanol solvent containing a carbon source;
[0007] S2: adding a zirconium source and a lithium source to the carbon source-containing ethanol solvent, and stirring in a stirring tank to uniformly disperse the zirconium source and the lithium source in the ethanol solution to form a uniform mixed suspension;
[0008] S3: adding acetonitrile to the mixed suspension, and heating the mixed suspension in the stirring kettle, and continuously stirring during the heating process until a white viscous substance appears in the stirring kettle;
[0009] S4: adding a lithium source, an iron source, a cobalt source, a manganese source, a phosphorus source and deionized water into a stirred tank, stirring continuously, mixing evenly, and preparing a mixed slurry;
[0010] S5: further mixing the mixed slurry by ball milling, and spray drying the mixed slurry by spray drying to prepare a ternary composite olivine structure positive electrode material precursor of lithium zirconate coated with iron, cobalt and manganese;
[0011] S6: placing the ternary composite olivine structure positive electrode material precursor in a high-temperature sintering furnace and calcining it under inert atmosphere conditions to obtain a ternary composite olivine structure positive electrode material of lithium zirconate coated with iron, cobalt and manganese.
[0012] Furthermore, in step S1, the carbon source includes one or more of glucose, sucrose, citric acid and polyethylene glycol, and the carbon source is 3-7% m / v of the ethanol solvent.
[0013] Furthermore, in step S2, the zirconium source includes one or more of zirconium nitrate pentahydrate, hydrated zirconium oxynitrate, zirconium sulfate and zirconium phosphate, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium dihydrogen phosphate, the molar ratio of the zirconium element to the lithium element is 1:2 to 2.3, and the solid content of the mixed suspension is 20 to 60%.
[0014] Furthermore, in step S3, the amount of acetonitrile is 1-10% v / v of the ethanol solvent, and the stirring kettle is heated at 50-100°C.
[0015] Further, in step S4, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium dihydrogen phosphate, the iron source includes one or both of ferric phosphate and ferrous oxalate, the manganese source includes one or both of manganese phosphate and manganese carbonate, the cobalt source includes one or both of cobalt phosphate and cobalt carbonate, the phosphorus source includes one or both of phosphoric acid and diammonium phosphate, the molar ratio of lithium / (iron+cobalt+manganese) / phosphorus in the mixed slurry is 1-1.15:0.96-1:1, and the deionized water is used to adjust the solid content in the mixed slurry, and the solid content of the mixed slurry is 30-60%.
[0016] Furthermore, in step S5, the ball milling time is 2 to 8 hours, and the temperatures of the material inlet and outlet during the spray drying process of the spray dryer are 200 to 230° C. and 60 to 100° C. respectively.
[0017] Furthermore, in step S6, the inert atmosphere includes one or both of nitrogen and argon, the calcination temperature is 600-800° C., and the calcination time is 8-24 hours.
[0018] Beneficial effects of the present invention:
[0019] The present invention adopts the method of stirring, heating, ball milling, spray drying and calcining to prepare the positive electrode material. The preparation process is simple, the process is easy to control, and the preparation cost is low. The method can form a modified lithium phosphate metal material structure on the outer surface of the lithium iron phosphate positive electrode material. The structure is stable, and the excessive dissolution of metal can be prevented, thereby improving the material cycle performance and safety performance.
[0020] The present invention combines metal phosphate solid solutions of different components to construct a multi-dimensional conductive network on the surface of lithium iron phosphate particles, which can greatly reduce the contact change between the electrode and the electrolyte and the volume expansion during discharge, and can effectively solve the problem of high capacity loss in the discharge cycle;
[0021] The positive electrode material of the present invention is a ternary composite olivine material coated with lithium zirconate, which is a multimodal porous material covered with micropores, mesopores and macropores, which increases the specific surface area of the material and improves the transfer speed of ions and electrons during charging and discharging;
[0022] The present invention adopts iron, cobalt and manganese metal materials, which greatly reduces the problem of high toxicity of electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a flow chart for the preparation of composite olivine structure positive electrode materials. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1
[0027] In this embodiment, lithium carbonate is used as a lithium source, anhydrous iron carbonate, manganese carbonate, and cobalt carbonate are used as iron sources, manganese sources, and cobalt sources, zirconium nitrate pentahydrate is used as a zirconium source, phosphoric acid is used as a phosphorus source, and glucose and polyethylene glycol are used as carbon sources. Figure 1 As shown, the following steps are used to prepare a lithium zirconate-coated iron, cobalt, and manganese ternary composite olivine positive electrode material;
[0028] S1: Add ethanol as a solvent to a stirred tank, and during continuous stirring, slowly add glucose and polyethylene glycol to the ethanol solvent in sequence, and stir evenly until completely dissolved to form a carbon source-containing ethanol solvent, wherein the mass ratio of glucose to polyethylene glycol is 1:1, and the glucose and polyethylene glycol are 5% of the ethanol solvent;
[0029] S2: adding lithium acetate and zirconium nitrate pentahydrate in a molar ratio of 2:1 to the carbon source-containing ethanol solvent, stirring in a stirred tank to uniformly disperse the lithium acetate and zirconium nitrate pentahydrate in the ethanol solution to form a uniform mixed suspension, wherein the solid content is 25%;
[0030] S3: adding acetonitrile accounting for 2% of the ethanol solvent to the mixed suspension, and heating the mixed suspension in the stirred tank to 70° C., and continuously stirring during the heating process until a white viscous substance appears in the stirred tank;
[0031] S4: adding anhydrous iron carbonate, manganese carbonate, cobalt carbonate and deionized water into a stirring kettle, stirring for 20 minutes, slowly adding phosphoric acid after stirring evenly, and slowly adding lithium acetate after the reaction is complete, stirring for 30 minutes, and stirring for 30 minutes to form a mixed slurry, wherein the solid content of the mixed slurry is adjusted to 40% by deionized water;
[0032] S5: After ball milling the mixed slurry for 4 hours, the mixed slurry is spray dried by a spray dryer at an inlet temperature of 210° C. and an outlet temperature of 90° C. to prepare a ternary composite olivine structure positive electrode material precursor of lithium zirconate coated with iron, cobalt and manganese, wherein the molar ratio of lithium / (iron+manganese+cobalt) / phosphorus is 1.05:1:1, and the molar ratio of iron / cobalt / manganese is 5:2.5:2.5;
[0033] S6: The precursor of the ternary composite olivine structure positive electrode material is placed in a high-temperature sintering furnace and calcined at 750°C for 12 hours under inert atmosphere conditions. The obtained lithium zirconate coated iron, cobalt and manganese ternary composite olivine structure positive electrode material is recorded as LEMCP-S1.
[0034] Example 2
[0035] In this embodiment, the molar ratio of iron / cobalt / manganese is adjusted to 6:2:2, and the remaining preparation steps are carried out with reference to Example 1. The obtained lithium zirconate-coated iron, cobalt, and manganese ternary composite olivine structure positive electrode material is recorded as LEMCP-S2.
[0036] Example 3
[0037] In this embodiment, the molar ratio of iron / cobalt / manganese is adjusted to 7:1.5:1.5, and the remaining preparation steps are carried out with reference to Example 1. The obtained lithium zirconate coated iron, cobalt, and manganese ternary composite olivine structure positive electrode material is recorded as LEMCP-S3.
[0038] Example 4
[0039] In this embodiment, the molar ratio of iron / cobalt / manganese is adjusted to 8:1:1, and the remaining preparation steps are carried out with reference to Example 1. The obtained lithium zirconate coated iron, cobalt, and manganese ternary composite olivine structure positive electrode material is recorded as LEMCP-S4.
[0040] Example 5
[0041] In this embodiment, the molar ratio of iron / cobalt / manganese is adjusted to 9:0.5:0.5, and the remaining preparation steps are carried out with reference to Example 1. The obtained lithium zirconate coated iron, cobalt, and manganese ternary composite olivine structure positive electrode material is recorded as LEMCP-S5.
[0042] Example 6
[0043] In this embodiment, no zirconium source is added, no lithium zirconate coating is performed, lithium carbonate is used as the lithium source, ferrous oxalate, manganese phosphate and cobalt phosphate are used as the iron source, manganese source and cobalt source respectively, sucrose and polyethylene glycol are used as carbon sources, and the iron, cobalt and manganese ternary composite olivine positive electrode material is prepared according to the following steps;
[0044] S1: Add ethanol as a solvent to a stirred tank, and during continuous stirring, slowly add sucrose and polyethylene glycol to the ethanol solvent in sequence, and stir evenly until completely dissolved to form a carbon source-containing ethanol solvent, wherein the mass ratio of sucrose to polyethylene glycol is 1:1, and the sucrose and polyethylene glycol are 5% of the ethanol solvent;
[0045] S2: Add ferrous oxalate, manganese carbonate, cobalt carbonate and deionized water into a stirring kettle, stir for 20 minutes, slowly add phosphoric acid after stirring evenly, continue stirring for 30 minutes after the reaction is complete, then slowly add lithium carbonate, continue stirring for 30 minutes to form a mixed slurry, wherein the solid content of the mixed slurry is adjusted to 40% by using deionized water;
[0046] S5: After ball milling the mixed slurry for 4 hours, the mixed slurry is spray dried using a spray dryer at an inlet temperature of 210° C. and an outlet temperature of 90° C. to prepare a ternary composite olivine structure cathode material precursor of iron, cobalt, and manganese, wherein the molar ratio of lithium / (iron+manganese+cobalt) / phosphorus is 1.05:1:1, and the molar ratio of iron / cobalt / manganese is 5:2.5:2.5;
[0047] S6: The precursor of the ternary composite olivine structure cathode material is placed in a high-temperature sintering furnace and calcined at 750° C. for 12 h under inert atmosphere conditions. The obtained iron, cobalt and manganese ternary composite olivine structure cathode material is recorded as LEMCP-D1.
[0048] Example 7
[0049] In this embodiment, no cobalt source is added, lithium carbonate, anhydrous iron phosphate, zirconium sulfate and manganese carbonate are used as lithium source, iron source, zirconium source and manganese source respectively, phosphoric acid is used as phosphorus source, citric acid and polyethylene glycol are used as carbon source, and lithium zirconate coated iron, manganese binary composite olivine positive electrode material is prepared according to the following steps;
[0050] S1: Add ethanol as a solvent to a stirred tank, and during continuous stirring, slowly add citric acid and polyethylene glycol to the ethanol solvent in sequence, and stir evenly until completely dissolved to form a carbon source-containing ethanol solvent, wherein the mass ratio of citric acid to polyethylene glycol is 1:1, and the citric acid and polyethylene glycol are 5% of the ethanol solvent;
[0051] S2: adding lithium carbonate and zirconium sulfate in a molar ratio of 2:1 to the carbon source-containing ethanol solvent, stirring in a stirred tank to uniformly disperse the lithium carbonate and zirconium sulfate in the ethanol solution to form a uniform mixed suspension with a solid content of 25%;
[0052] S3: adding acetonitrile accounting for 2% of the ethanol solvent to the mixed suspension, and heating the mixed suspension in the stirred tank to 70° C., and continuously stirring during the heating process until a white viscous substance appears in the stirred tank;
[0053] S4: adding anhydrous iron carbonate, manganese carbonate and deionized water into a stirring kettle, stirring for 20 minutes, slowly adding phosphoric acid after stirring evenly, and slowly adding lithium carbonate after the reaction is complete, stirring for 30 minutes, and stirring for 30 minutes to form a mixed slurry, wherein the solid content of the mixed slurry is adjusted to 40% by deionized water;
[0054] S5: After ball milling the mixed slurry for 4 hours, the mixed slurry is spray dried by a spray dryer at an inlet temperature of 210° C. and an outlet temperature of 90° C. to prepare a binary composite olivine structure positive electrode material precursor of lithium zirconate coated with iron and manganese, wherein the molar ratio of lithium / (iron+manganese) / phosphorus is 1.05:1:1, and the molar ratio of iron / manganese is 7.5:2.5;
[0055] S6: The binary composite olivine structure positive electrode material precursor is placed in a high-temperature sintering furnace and calcined at 750° C. for 12 hours under inert atmosphere conditions. The obtained binary composite olivine structure positive electrode material of lithium zirconate coated with iron and manganese is recorded as LEMP-D2.
[0056] Example 8
[0057] In this embodiment, no manganese source is added, and lithium carbonate, phosphoric acid, cobalt carbonate, zirconium nitrate pentahydrate and anhydrous ferric phosphate are used as lithium source, phosphorus source, cobalt source, zirconium source and iron source, and glucose and polyethylene glycol are used as carbon sources. The molar ratio of iron / cobalt is adjusted to 7.5:2.5, and the remaining preparation steps are carried out with reference to Example 7. The obtained lithium zirconate coated iron, cobalt binary composite olivine structure positive electrode material is recorded as LFCP-D3.
[0058] Example 9
[0059] In this embodiment, no manganese source and cobalt source are added. Lithium carbonate, zirconium nitrate pentahydrate and anhydrous ferric phosphate are used as lithium source, zirconium source and iron source, glucose and polyethylene glycol are used as carbon sources, and the remaining preparation steps are carried out with reference to Example 7. The prepared lithium zirconate-coated lithium iron phosphate positive electrode material is recorded as LFP-D4.
[0060] Example 10
[0061] In this embodiment, no iron source and cobalt source are added. Lithium carbonate, zirconium nitrate pentahydrate, anhydrous manganese carbonate and phosphoric acid are used as lithium source, zirconium source, manganese source and phosphorus source, glucose and polyethylene glycol are used as carbon sources, and the remaining preparation steps are carried out with reference to Example 7. The prepared lithium zirconate-coated lithium manganese phosphate positive electrode material is recorded as LMP-D5.
[0062] Embodiment 11
[0063] In this embodiment, no iron source and manganese source are added. Lithium carbonate, zirconium nitrate pentahydrate, cobalt carbonate and phosphoric acid are used as lithium source, zirconium source, cobalt source and phosphorus source. Glucose and polyethylene glycol are used as carbon sources. The remaining preparation steps are carried out with reference to Example 7. The prepared lithium zirconate-coated lithium cobalt phosphate positive electrode material is recorded as LCP-D6.
[0064] In summary, the data parameters of Examples 1 to 11 are shown in Table 1 below:
[0065] Comparing Example 1 with Example 6, it can be seen that the iron-cobalt-manganese electrode combined with lithium zirconate has better performance;
[0066] By comparing Example 1 with Examples 7 to 11, it can be seen that the performance of the iron-cobalt-manganese electrode combined with lithium zirconate is better than that of the non-iron-cobalt-manganese electrode combined with lithium zirconate;
[0067] By comparing Examples 1 to 5 with Examples 7 to 11, it can be seen that when the total amount of iron, cobalt and manganese is the same, no matter how the iron, cobalt and manganese ratio is adjusted, the performance of the iron, cobalt and manganese electrode is better than that of the non-iron, cobalt and manganese electrode.
[0068] Table 1:
[0069]
[0070] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite olivine structure positive electrode material, characterized in that: The steps include: S1: adding ethanol as a solvent to a stirred tank, adding a carbon source to the ethanol solvent during continuous stirring, and stirring evenly to completely dissolve the carbon source in the ethanol solvent to form an ethanol solvent containing a carbon source; S2: adding a zirconium source and a lithium source to the carbon source-containing ethanol solvent, and stirring in a stirring tank to uniformly disperse the zirconium source and the lithium source in the ethanol solution to form a uniform mixed suspension; S3: adding acetonitrile to the mixed suspension, and heating the mixed suspension in the stirring kettle, and continuously stirring during the heating process until a white viscous substance appears in the stirring kettle; S4: adding a lithium source, an iron source, a cobalt source, a manganese source, a phosphorus source and deionized water into a stirred tank, stirring continuously, mixing evenly, and preparing a mixed slurry; S5: further mixing the mixed slurry by ball milling, and spray drying the mixed slurry by spray drying to prepare a ternary composite olivine structure positive electrode material precursor of lithium zirconate coated with iron, cobalt and manganese; S6: placing the ternary composite olivine structure positive electrode material precursor in a high-temperature sintering furnace and calcining it under inert atmosphere conditions to obtain a ternary composite olivine structure positive electrode material of lithium zirconate coated with iron, cobalt and manganese.
2. The method for preparing a composite olivine structure positive electrode material according to claim 1, characterized in that: In step S1, the carbon source includes one or more of glucose, sucrose, citric acid and polyethylene glycol, and the amount of the carbon source added is 3-7% m / v of the ethanol solvent.
3. The method for preparing a composite olivine structure positive electrode material according to claim 1, characterized in that: In step S2, the zirconium source includes one or more of zirconium nitrate pentahydrate, hydrated zirconium oxynitrate, zirconium sulfate and zirconium phosphate, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium dihydrogen phosphate, the molar ratio of the zirconium element to the lithium element is 1:2 to 2.3, and the solid content in the mixed suspension is 20 to 60%.
4. The method for preparing a composite olivine structure positive electrode material according to claim 1, characterized in that: In step S3, the amount of acetonitrile used is 1-10% v / v of the ethanol solvent, and the stirring kettle is heated at 50-100°C.
5. The method for preparing a composite olivine structure positive electrode material according to claim 1, characterized in that: In step S4, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium dihydrogen phosphate, the iron source includes one or both of ferric phosphate and ferrous oxalate, the manganese source includes one or both of manganese phosphate and manganese carbonate, the cobalt source includes one or both of cobalt phosphate and cobalt carbonate, the phosphorus source includes one or both of phosphoric acid and diammonium phosphate, the molar ratio of lithium / (iron+cobalt+manganese) / phosphorus in the mixed slurry is 1-1.15:0.96-1:1, and the deionized water is used to adjust the solid content in the mixed slurry to 30-60%.
6. The method for preparing a composite olivine structure positive electrode material according to claim 1, characterized in that: In step S5, the ball milling time is 2 to 8 hours, and the temperatures of the material inlet and outlet during the spray drying process of the spray dryer are 200 to 230° C. and 60 to 100° C. respectively.
7. The method for preparing a composite olivine structure positive electrode material according to claim 1, characterized in that: In step S6, the inert atmosphere includes one or both of nitrogen and argon, the calcination temperature is 600-800° C., and the calcination time is 8-24 hours.